(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
With the development of laser technologies, the field of application of lasers is developing as well. They are capable of processing numerous materials and are still finding their application in unexpected areas. In this case, lasers are studied as a system with which black and white color artificial leather can be processed. This modern material allows you to combine comfort, practicality and reasonable price in a finished product. The manufacturer of artificial leather provides wide possibilities of design. In this study laser beam was used for dark and light laser markings on black and white color artificial leather and in this work, it could be observed how CO2 and fiber laser processing influence this specific material.